Development of Adobe Flash-Based Learning Media Integrated with Local Wisdom to Improve Literacy, Learning Interest and Moral Character of Students in Integrated Islamic Elementary Schools - Deni Hazmi; Siti Halimah; Yusnaili Budianti (Universitas Islam Negeri Palopo, 2026)
This study aims to develop interactive learning media based on Adobe Flash CS6 integrated with Malay Deli local wisdom to improve students’ learning interest and moral character in Islamic Religious Education (PAI) learning at an Integrated Islamic Elementary School. The background of this research is rooted in the limited use of innovative media in elementary Islamic education, where conventional teaching methods often lead to low student engagement and weak internalization of moral values. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The study was conducted at SD IT Ummi A’yuni, Perbaungan, North Sumatra, involving fifth-grade students, teachers, and expert validators. Data collection techniques included observation, interviews, questionnaires, validation sheets, and learning outcome assessments. The developed media integrated multimedia elements such as text, animation, audio, video, and interactive quizzes with local cultural values reflecting Malay Deli traditions, politeness, cooperation, and Islamic ethics. The findings revealed that the media achieved a high level of feasibility based on evaluations by media experts, language experts, and subject matter experts. Students demonstrated increased enthusiasm, participation, and understanding of moral concepts during the learning process. Furthermore, the use of Adobe Flash-based interactive media significantly enhanced students’ learning interest and strengthened their understanding of commendable moral behavior. The study concludes that integrating technology with local wisdom can create meaningful, contextual, and engaging learning experiences while simultaneously supporting character education in elementary Islamic schools. The findings also indicate that technology-based media can become an effective pedagogical innovation for strengthening Islamic values, student motivation, and culturally responsive education in the twenty-first century.